Analysis of the socio-environmental actions developed by agribusiness public organizations operating in the municipality of São Gabriel- RS - Cunha, Indiara Barcellos da; Barata, Ana Júlia Sarmento; Alves, Ricardo Ribeiro (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The post-Industrial Revolution era marked the beginning of swelling populations in the big centers, the arrival of technologies and, consequently, environmental imbalance. During the XX century, there were intense debates on the problems of exploring the natural resources, at the Stockholm Conference. Currently, the economy sectors have pursued more sustainable innovations and strategies, which is the case of agribusiness and in light of this fact, the objective of the present paper consists in characterizing the socio-environmental actions developed by public organizations of agribusiness, operating in the municipality of São Gabriel (RS). We conducted a bibliographic research including books and scientific articles on Public Administration and Agribusiness Organizations. Later, an itinerary of interviews was created, comprising 14 questions, split into two groups: group 1 Public Administration and group 2 Public Administration at Agribusiness. Technicians of the following four organizations were interviewed: EMATER, IRGA, FEPAGRO and the Municipal Secretariat of Agriculture. After analyzing the data collection tool, it was concluded that the interviewed organizations are committed to developing socio-environmental actions in their extension activities, by IRGA and EMATER institutions, in the research segment, by FEPAGRO and disseminating agents of social and political programs, by the Municipal Secretariat of Agriculture of São Gabriel (RS).